Qualitative Secondary Analysis: Building Longitudinal Samples to Understand Men's Generational Identities in Low Income Contexts. (June 2019) - Tarrant, Anna; Hughes, Kahryn
There have been significant developments in methods of qualitative secondary analysis (QSA), prompted in part by growth in infrastructure for archiving and sharing qualitative data, facilitating reuse. Building from these developments, this article presents QSA that brings together subsamples of men in low income contexts from two qualitative longitudinal datasets produced under Timescapes, demonstrating the complex linkages between them, and addressing two key questions. First, in bringing these two datasets together, is it possible to build an intergenerational sample of men in low income contexts to further our understanding of their generational identities and intergenerational experiences? Second, what sorts of intergenerational, or intragenerational, analyses are possible? We conclude that it was not possible to build a straightforwardly vertical intergenerational sample, but intragenerational cohort analyses of generational identities have enabled insights into the dynamic relational processes productive of longitudinal experiences of marginalization and vulnerability for men living in low income contexts.